2006
DOI: 10.1590/s1415-47572006000100008
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of 677C -> T and 1298A -> C polymorphisms in the 5,10-methylenetetrahydrofolate reductase (MTHFR) gene in Turner syndrome individuals

Abstract: Turner syndrome (TS) is an interesting model for investigating the association between methylenetetrahydrofolate reductase (MTHFR) gene polymorphisms and non-disjunction because of the high frequency of chromosomal mosaicism among patients with this syndrome. We determined the frequencies of MTHFR 677C ® T and 1298A ® C polymorphic mutations in 49 patients with TS and 200 control individuals. The frequency of the 677C ® T allele was 0.39 for patients and 0.29 for controls while that of the 1298A ® C allele was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 13 publications
2
8
0
1
Order By: Relevance
“…The present observations are in confl ict with previous results of the literature, studying less than 50 TS patients with multiple karyotype presentation (13). Some considerations may be done related to the small sample of TS patients and the heterogeneity of the control group.…”
Section: Discussionsupporting
confidence: 88%
“…The present observations are in confl ict with previous results of the literature, studying less than 50 TS patients with multiple karyotype presentation (13). Some considerations may be done related to the small sample of TS patients and the heterogeneity of the control group.…”
Section: Discussionsupporting
confidence: 88%
“…28---30 The results regarding the contribution of these polymorphisms to the etiology of TS are conflicting, as the C677T SNP was associated with TS in one study, 28 whereas in the others it was A1298C. 28---30 The results regarding the contribution of these polymorphisms to the etiology of TS are conflicting, as the C677T SNP was associated with TS in one study, 28 whereas in the others it was A1298C.…”
Section: Chromosomal Nondisjunctionmentioning
confidence: 99%
“…Santos et al [2006] evaluated the frequencies of the MTHFR 677T and 1298 C polymorphic mutations in 49 TS patients and 200 controls, and reported that the 677TT genotype was found significantly more frequently among Turner patients. Santos et al [2006] evaluated the frequencies of the MTHFR 677T and 1298 C polymorphic mutations in 49 TS patients and 200 controls, and reported that the 677TT genotype was found significantly more frequently among Turner patients.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with Turner syndrome (TS) show a high frequency of chromosome mosaicism [Santos et al, 2006], and thus represent an interesting model in which to investigate the effects of folate pathway polymorphisms as possible risk factors for somatic chromosomal nondisjunction. TS is characterized by the absence or abnormality of one sex chromosome in either all or some cells.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation